KOPI SAJANG MENUJU DUNIA MELALUI PROMOSI DAN PEMBAHARUAN KEMASAN PRODUK SAJANG’S COFFEE TO WORLD THROUGH PROMOTION AND RENEWAL OF PACKAGING PRODUCTS - muhamad Sarjan (Jurnal Warta Desa (JWD), 2019)
Sembalun affections village subdistrict East Lombok district is a village located on the north slope of Mount Rinjani. The village has an excellent coffee commodity. However, there are some problems faced by coffee producers in this village, one of which is a matter of marketing. Village location away from the city made the affections of coffee marketing is constrained. This problem can be overcome by making a promotional tool. A promotional tool here can be a pamphlet, social media and so forth. Making the affections coffee social media aims to facilitate the promotion and the coffee can be known more widely. The method used is the preparation of the program, the renewal of affections coffee product packaging and manufacturing of social media such as instagram.